(untitled) - Westra, Richard (New York, 2003)
This volume offers a unique cross-fertilization of two of the most important literatures in critical political economy: debates over the theory of political economy and the concrete analysis of the world economy today. In meeting this challenge, the volume assembles innovative and original work from leading scholars who have written extensively on both topics. Together, the contributors bring a rich variety of intellectual traditions and perspectives to bear on this historical turning point in the global system. The issues they address include transformations in the technical and social organization of production, the rise of global finance, the changing character of globalization, the anatomy of economic crisis and market failure, the impact of consumerism on human subjectivity, and the desperate need for alternatives to mainstream economic analysis.
Keywords: Value,Capitalism,Marxian economics,Production (economic theory),International economic relations,Globalization,Financial crises,Economic history; Economic aspects,History; 21st century,21st century